Size-induced segregation during die filling - A. Zakhvatayeva; C. Hare; C.Y. Wu (Elsevier, 2019)
The present study investigated particle size-induced segregation during die filling of binary pharmaceutical blends, consisting of fine and coarse particles in various fractions. Coarse fraction was made of milled and sieved acetylsalicylic acid, whereas the fine fraction was mannitol. The die filling process was carried out in gravity filling and suction filling. The segregation was assessed through determination of the coarse component concentration using UV-Visible spectrophotometry. The obtained values of concentration, determined for ten units of identical volume inside the die, were used to calculate the segregation index (SI), which was an indicator of uniformity of the powder blend deposited into the die. It was found that high segregation tendency was generally observed during gravity filling at a low velocity, due to the effect of air drag, and during gravity filling at a high velocity, as it was carried out through three consecutive filling steps. The lowest segregation tendency was generally observed during suction filling at a low velocity. The horizontal segregation was mostly observed in the top layers of the die, due to mainly two mechanisms: coarse particles cascading down the heap formed by the powder in the final steps of die filling, which produces higher coarse concentration at the near side of the die, observed at low coarse concentration; or coarse particle cascading down the top surface of the flowing powder stream into the die, which increases the coarse concentration at the far end of the die. Keywords: Segregation, Particle size, Die filling, Tabletting, Powder flow